Mafhum Muwafaqah dan Implikasinya Terhadap Masalah-Masalah Furu’iyyah - Mawardi Mawardi (Hukum Islam, 2021)
This paper is motivated by differences of opinion about the validity of mafhm muwâfaqaħ which has implications for the establishment of law in matters of furu'iyyah. The existence of the theory of mafhum muwafaqah is in the level of the concept of dilalah al-alfazh among mutakallimin, especially in the view of Syafi'iyyah scholars that this theory of mafhum muwâfaqaħ is a connotation of understanding of the law mentioned in lafazh also applies to the problem law that is not mentioned lafazh. In terms of the strength of law enforcement, mafhûm muwâfaqaħ is divided into two, namely; mafhum aulawi,  is called fahw al-khithâb and mafhum al-musawiy, is called lahn al-khithâb. Scholars who recognize the blasphemy of mafhum muwafaqah say that the application of the law takes two forms: First, through lafzhiyyah and qiyas jaliy. Therefore, research needs to be done because the results of istinbath law that most "approach" the truth through the passage of the texts are to understand the full meaning of the texts to a law, cannot be understood in bits and pieces.